2012
DOI: 10.3109/15563650.2012.731510
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal poisonings with methadone in France: Results of a two year national survey by the Toxicovigilance Network

Abstract: In France, suicide attempts were more likely to occur with the capsule formulation. The clinical severity of intoxication was similar between the capsule and liquid forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The study on galenic methadone formulations confirmed previously published results [1,2]. Formulation was provided in 1127 files (80% of the series), with 629 (55.8%) cases involving methadone capsules and 498 (36%) cases involving methadone syrup.…”
Section: Comparison Between Methadone Capsules Vs Methadone Syrupsupporting
confidence: 83%
See 3 more Smart Citations
“…The study on galenic methadone formulations confirmed previously published results [1,2]. Formulation was provided in 1127 files (80% of the series), with 629 (55.8%) cases involving methadone capsules and 498 (36%) cases involving methadone syrup.…”
Section: Comparison Between Methadone Capsules Vs Methadone Syrupsupporting
confidence: 83%
“…This series of methadone exposures on a national scale is one of the largest compiled series in international medical literature. It enabled the clarification or confirmation of several notions which had already been highlighted in two previous papers involving the experience of poison centres in France on methadone exposure [1,2]. First of all, it confirms that methadone is not a harmless drug: this molecule is responsible for serious and sometimes fatal accidents happening to children [2] and is just as dangerous for adults.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Concerning drug-related deaths, for example in France, data collected in the framework of DRAMES (relationship with death and drugs or substance abuse [décès en relation avec l'abus de médicaments et de substances]) do not cover all drug-related deaths in the country. [41] By contrast, in Scandinavian countries such as Finland or Norway, toxicological analyses are recorded in a national exhaustive registry. [42,43] Launiainen et al found that pregabalin was identified as frequently as oxycodone in deaths occurring in young population (15-34 years), with two thirds of these deaths related with abuse.…”
Section: Toxicology Databasesmentioning
confidence: 99%